Implementation of 'Safe from Harm' in Scouting to Support Students Mental Health - Sabiq, Zamzami (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The mental health of students has become a growing concern due to increasing pressures from academic demands, social interactions, and social media. This study focuses on the role of Scouting activities as an extracurricular activity in supporting students' mental health through preventive and promotive strategies. The goal is to assess the impact of Scouting activities in developing mental resilience, enhancing social skills, and implementing the Safe from Harm principle introduced by the World Organization of the Scout Movement (WOSM) to ensure psychological safety. This study uses a qualitative approach, gathering data through interviews, observations, and documentation from the East Java Scout Movement Regional Office. The analysis indicates that Scouting activities effectively enhance communication skills, self-confidence, and create a secure environment through the Safe from Harm principle. Challenges include limited training and awareness among instructors and inadequate infrastructure in rural areas. Suggested solutions include regular training sessions, reinforcing context-specific security policies, and fostering external collaborations. The findings of this study underscore the significance of Scouting activities as an effective approach to supporting students' mental health.